Biomarkers of potential harm in people switching from smoking tobacco to exclusive e-cigarette use, dual use, or abstinence: secondary analysis of Cochrane systematic review of trials of e-cigarettes for smoking cessation - Hartmann-Boyce, J; Butler, AR; Theodoulou, A; Onakpoya, IJ; Hajek, P; Bullen, C; Rigotti, NA; Lindson, N (Wiley, 2022)
Aims This study aims to compare biomarkers of potential harm between people switching from smoking combustible cigarettes (CC) completely to electronic cigarettes (EC), continuing to smoke CC, using both EC and CC (dual users) and using neither (abstainers), based on behaviour during EC intervention studies.